Food insecurity as a supply chain problem. Evidence and lessons from the production and supply of bananas in Uganda - Ssennoga, Francis; Mugurusi, Godfrey; Nagitta Oluka, Pros (Scientific African, 2019)
Despite agriculture being the main economic activity in Uganda, increasing food prices within the country point to the growing challenge of food insecurity. In 2016, food short- age was reported in some parts of Uganda (mainly in Karamoja sub-region and parts of Serere) and government resorted to temporary relief distribution of food from other re- gions of the country. The acute food shortage in one part of the country while another part, a few hundred kilometers away, has excess farm output calls into question the effi- ciency of the supply chain of some agro-commodities. This research attempts to examine the challenges faced in the production and supply of bananas in Uganda and how the supply chain perspective can help us address these challenges better. We juxtapose the supply chain approach against the value chain per- spective and argue that the supply chain perspective offers a much deeper understanding of market-based challenges, which affect livelihoods of smallholders who often sell their products at rock-bottom prices. A cross sectional survey of various banana production and consumptions points in Uganda was conducted. The findings show that losses in the supply chain accounted for about 29% of banana production –a figure slightly lower than that 40% previously reported in the literature. In addition, the farmers did not benefit from increased food prices due to inadequate market information at their disposal despite banana value chains having re- cently received significant development attention. We also found that infrastructural bot- tlenecks and limited collaboration and coordination among smallholders heavily affected the supply of bananas in the country. This is arguably a key factor that strongly explains the food insecurity problem in Uganda. We conclude that the findings point to a different problem, which is that of a dysfunctional supply chain structure of bananas from the rural areas to urban centres in Kampala.
Keywords: Bananas; Banana supply chains; Supply chain approach; Value chain approach; Food security; Agriculture